Adverse drug events associated with capecitabine: a real-world pharmacovigilance study based on the FAERS database - Rongqiang Liu; Yukai Chen; Shi-Nan Wu; Wangbin Ma; Zhendong Qiu; Jianguo Wang; Ximing Xu; Chen Chen; Weixing Wang (Therapeutic Advances in Drug Safety)
Background: Capecitabine, a prodrug of 5-fluorouracil, is extensively utilized for the treatment of metastatic breast cancer, colorectal cancer, and gastric cancer. Nevertheless, there exist limitations in comprehending adverse reactions (AEs) in clinical practice. In this study, we investigated the distribution of AEs associated with capecitabine and explored potential rare adverse reactions by mining the Food and Drug Administration Adverse Event Reporting System (FAERS). Objectives: Our research aimed to explore the spectrum of AEs associated with capecitabine, including both documented and potential events, to provide a comprehensive understanding of the drug’s safety profile and guide clinical practice. At the same time, it provides a new direction for further research on AEs associated with capecitabine in the future. Design: We collected capecitabine-related adverse reactions from the FAERS and standardized the classification of AEs using the Medical Dictionary for Regulatory Activities 26.0. Four statistical schemes were used to analyze the obtained standardized signals. Methods: We collected AEs reported for capecitabine from the FAERS between 2004 and 2023. To ensure standardized data, the collected reports related to capecitabine-associated adverse events were categorized using the preferred terms (PTs) and system organ classes (SOCs) classifications provided by the Medical Dictionary for Regulatory Activities 26.0. Statistical analysis involved the utilization of reporting odds ratio, proportional reporting ratio, Bayesian confidence propagation neural network, and multi-item gamma Poisson shrinker. Four statistical schemes were employed to analyze the adverse reactions associated with capecitabine. A positive signal was considered when all four schemes indicated an association with the adverse event. Results: We collected a total of 45,011 AEs associated with the use of capecitabine from the database, covering 27 SOCs from 2004 to 2023. The nine SOC categories with the highest number of events were identified, which include gastrointestinal disorders; general disorders and administration site conditions; skin and subcutaneous tissue disorders; nervous system disorders; investigations, injury, poisoning, and procedural complications; blood and lymphatic system disorders; metabolism and nutrition disorders; infections and infestations; and neoplasms benign, malignant, and unspecified (including cysts and polyps). Among these 27 SOCs, we identified seven SOCs that met the signal value criteria. Notably, we discovered AEs not mentioned in the instructions, including intestinal obstruction in gastrointestinal disorders, penetrating aortic ulcer in cardiac disorders, and non-cirrhotic portal hypertension in hepatobiliary disorders, all of which exhibited signals. Furthermore, 40.1% of AEs associated with the use of capecitabine occurred within the first 30 days. Conclusion: Our study conducted a comprehensive analysis of capecitabine’s AEs using the FAERS database. We identified previously unreported AEs, mitigating the risk for patients and ensuring safe drug administration.